Integrating transcriptomic and proteomic analyses of photoperiod-sensitive in near isogenic maize line under long-day conditions - Xiao-heng SONG; Lei TIAN; Shun-xi WANG; Jin-long ZHOU; Jun ZHANG; Zan CHEN; Liu-ji WU; Li-xia KU; Yan-hui CHEN (Journal of Integrative Agriculture)
As a short-day plant species, maize requires an optimal photoperiod for inducing reproductive growth. However, there is a lack of information regarding photoperiod-induced changes in maize mRNA and protein levels. In this study, a photoperiod-insensitive maize inbred line and its near isogenic photoperiod-sensitive line were used. By integrating RNA-based transcriptomic and iTRAQ LC-MS/MS-based proteomic approaches, we generated a comprehensive inventory of the transcripts and proteins with altered abundances in response to a long photoperiod (LP) during growth stage transitions. We detected 22 000 transcripts in RNA-sequence runs and 5 259 proteins from an iTRAQ-based analysis. A weak correlation between mRNA- and protein-level changes was observed, suggesting the LP-induced transition between maize growth stages is largely regulated post-transcriptionally. Differentially expressed genes influenced by LP conditions were associated with several regulatory processes in both maize inbred lines, especially phosphate ion transport and the circadian rhythm. Additionally, 31 transcripts and six proteins related to photoperiodic flowering in maize were identified by comparing transcriptomic and proteomic data. This transcriptomic and proteomic analysis represents the first comprehensive and comparative study of gene/protein-level changes occurring in photoperiod-sensitive and -insensitive maize inbred lines during growth stage transitions under LP conditions.